The Shaking Palsy of the Larynx—Potential Biomarker for Multiple System Atrophy: A Pilot Study and Literature Review - Warnecke, Tobias; Vogel, Annemarie; Ahring, Sigrid; Gruber, Doreen; Heinze, Hans-Jochen; Dziewas, Rainer; Ebersbach, Georg; Gandor, Florin (Frontiers in Neurology, 2019)
In its early stages multiple system atrophy (MSA), a neurodegenerative movement disorder, can be difficult to differentiate from idiopathic Parkinson’s disease (PD), and emphasis has been put on identifying premotor symptoms to allow for its early identification. The occurrence of vegetative symptoms in addition to motor impairment, such as orthostatic hypotension and neurogenic bladder dysfunction, enable the clinical diagnosis in the advanced stages of the disease. Usually with further disease progression, laryngeal abnormalities become clinically evident and can manifest in laryngeal stridor due to impaired vocal fold motion, such as vocal fold abduction restriction, mostly referred to as vocal fold paresis, or paradoxical vocal fold adduction during inspiration. While the pathogenesis of laryngeal stridor is discussed controversially, its occurrence is clearly associated with reduced life expectancy. Before the clinical manifestation of laryngeal dysfunction however, abnormal vocal fold motion can already be seen in patients that might not yet fulfill the diagnostic criteria of MSA. In this article we summarize the current literature on pharyngolaryngeal findings in MSA and report preliminary findings from a pilot study investigating 8 consecutive MSA patients. Based on the available data and our preliminary clinical experience we developed a standardized easy-to-implement task-protocol to be performed during flexible endoscopic evaluation of swallowing (FEES) for detection of MSA-related pharyngolaryngeal abnormalities. Patients showed varying speech abnormalities. Only 2/8 patients exhibited laryngeal stridor. However, during FEES, all patients presented with irregular arytenoid cartilages movements and vocal fold abduction restriction. 3/8 showed vocal fold fixation and 1/8 paradoxical vocal fold motion. All patients presented with oropharyngeal dysphagia, 5/8 with penetration or aspiration events. We suggest that specific abnormal vocal fold motion can help identifying MSA patients and may allow for delimiting this disorder from idiopathic PD. These findings therefore may serve as a novel clinical biomarker for MSA. Based on the available data and our preliminary clinical experience we developed a standardized easy-to-implement task-protocol to be performed during flexible endoscopic evaluation of swallowing (FEES) for detection of MSA-related pharyngolaryngeal movement disorders. Furthermore, we initiated a prospective study to evaluate the diagnostic utility of this protocol.